Perbandingan Spektral Musik Klasik dengan Musik Etnik Jawa menggunakan Analisis MFCC dan Beat Strength: Dody Kurniawan, Ahmad Syakir, Hana Afifah, Rayhan Hanina, Iwan Yahya, Harjana - Dody Kurniawan, Dody Kurniawan; Ahmad Syakir, Ahmad Syakir; Hana Afifah, Hana Afifah; Rayhan Hanina, Rayhan Hanina; Iwan Yahya, Iwan Yahya; Harjana, Harjana (Jurnal Fisika dan Aplikasinya, 2025)
Spectral analysis between Javanese music and classical music by Mozart (1756-1791) using MFCC and Beat Strenght has been conducted. MFCC analysis using Hamming window and RGB conversion using similarity equation in visualization process. Beat Strength analysis based on PEAK and SUM value of Beat Histogram. The result shows that the pattern of classical music and Javanese music has 98.0% similarity for March of The Priests from The Magic Flute and 90.3% for Piano Sonata in C Major. Beat Strength analysis shows 89.8% similarity for March of The Priests from The Magic Flute and 72.6% for Piano Sonata in C Major.